(untitled) (Scientific journal of the Fergana State University, 2025)
This article analyzes the political situation in Khorasan after the death of Sultan Abu Sa’id Mirza, the ruler of the Timurid state, as well as the rivalry between the amirs of Samarkand and Herat. It also focuses on how Sultan Husayn Bayqara took advantage of this situation to seize the throne of Khorasan and strengthen his rule in the region. The analysis is based on primary historical sources and existing scholarly literature.